2004
DOI: 10.1186/ar1038
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 induces production of IL-6 and IL-8 in rheumatoid arthritis synovial fibroblasts via NF-κB- and PI3-kinase/Akt-dependent pathways

Abstract: Recent studies of the pathogenesis of rheumatoid arthritis (RA) have revealed that both synovial fibroblasts and T cells participate in the perpetuation of joint inflammation as dynamic partners in a mutual activation feedback, via secretion of cytokines and chemokines that stimulate each other. In this study, we investigated the role of IL-17, a major Th1 cytokine produced by activated T cells, in the activation of RA synovial fibroblasts. Transcripts of IL-17R (IL-17 receptor) and IL-17RB (IL-17 receptor B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 335 publications
(122 citation statements)
references
References 34 publications
10
111
0
1
Order By: Relevance
“…These results are consistent with previous reports indicating that both IL-6 and IL-17 activate STAT3 and NF-B (27,29,41). In addition, it was previously shown that the activation of both STAT3 and NF-B leads to the upregulation of Bcl-2 and Bcl-xL expression (26,42).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results are consistent with previous reports indicating that both IL-6 and IL-17 activate STAT3 and NF-B (27,29,41). In addition, it was previously shown that the activation of both STAT3 and NF-B leads to the upregulation of Bcl-2 and Bcl-xL expression (26,42).…”
Section: Discussionsupporting
confidence: 82%
“…The upregulation of prosurvival molecules in turn inhibited the apoptotic cell death of virus-infected cells and the destruction of virus epitope-bearing target cells by virus-specific CD8 ϩ T cells. The common signals involved in the upregulation caused by IL-6 and IL-17 were the activation of STAT3 and NF-B, although the signaling pathways for the activation are different between IL-6 and IL-17 (20,24,25,(27)(28)(29). These synergistic effects appear to be operational in TMEV-infected mice, as viral persistence in the CNS is partially enhanced after IL-17 administration and reduced after anti-IL-17 antibody treatment.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…IL-17A directly modulates fibroblast inflammatory functions by increasing IL-6, IL-8, G-CSF and matrix metalloproteinase production [14,15,16]. In vitro studies have also shown that rIL-17A did or did not upregulate the proliferation and collagen expression of cardiac or skin fibroblasts, respectively [17,18].…”
Section: Discussionmentioning
confidence: 99%